2006
DOI: 10.1002/hlca.200690214
|View full text |Cite
|
Sign up to set email alerts
|

Polarity‐Reversal‐Catalyzed Hydrostannylation Reactions: Benzeneselenol‐Mediated Homolytic Hydrostannylation of Electron‐Rich Olefins

Abstract: Dedicated to the memory of Professor Hanns Fischer. We take for granted his many contributions to the field of radical chemistry. I am particularly indebted to his careful and patient explaining to me of the persistent radical effect over a drink, on a balmy New Hampshire evening.Addition of 10 mol-% of diphenyl diselenide to hydrostannylation reactions involving electron-rich olefins results in a dramatic improvement in yield. For example, reaction of a-{[(tert-butyl)dimethylsilyl]-A C H T U N G T R E N N U N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…[54][55][56] High concentrations of stannane or polarity-reversal catalysis 57 is often required to effect free radical hydrostannylation, especially with bulky stannanes. 58,59 When low concentrations of tin hydride are used, the alkenyl radical arising from the addition of the tin-centered radical onto the alkyne (or alkene) cannot be trapped fast enough to compete with b-fragmentation to regenerate the carbon-carbon multiple bond, effectively increasing the likelihood of stannyl radical attack at sulfur (Scheme 11). When problems are encountered, these can usually be overcome through the use of more hindered tin hydrides to prevent addition to the alkene or alkyne as illustrated in Scheme 11, eqn (a) and (b).…”
Section: Chemoselectivity Principlesmentioning
confidence: 99%
“…[54][55][56] High concentrations of stannane or polarity-reversal catalysis 57 is often required to effect free radical hydrostannylation, especially with bulky stannanes. 58,59 When low concentrations of tin hydride are used, the alkenyl radical arising from the addition of the tin-centered radical onto the alkyne (or alkene) cannot be trapped fast enough to compete with b-fragmentation to regenerate the carbon-carbon multiple bond, effectively increasing the likelihood of stannyl radical attack at sulfur (Scheme 11). When problems are encountered, these can usually be overcome through the use of more hindered tin hydrides to prevent addition to the alkene or alkyne as illustrated in Scheme 11, eqn (a) and (b).…”
Section: Chemoselectivity Principlesmentioning
confidence: 99%
“…To our disappointment, initial attempts to hydrostannylate the enol ether 1 with tris[(1R,2S,5R)menthyl]tin hydride (tris[(1R,2S,5R)-2-(1-methylethyl)-5methylcyclohexyl]tin hydride) under radical conditions resulted in returned starting material, even in the presence of benzeneselenol as a polarity reversal catalyst. 4,5 In contrast, triphenylstannane afforded the product 2 in 20% yield and this could be improved to 95% in the presence of benzeneselenol. 5 Chiral free radical hydrostannylation reactions have been reported on a number of occasions; these reactions proceed most readily with electron-deficient alkenes, which is largely a consequence of the nucleophilicty of the stannyl radical.…”
Section: ' Introductionmentioning
confidence: 95%
“…4,5 In contrast, triphenylstannane afforded the product 2 in 20% yield and this could be improved to 95% in the presence of benzeneselenol. 5 Chiral free radical hydrostannylation reactions have been reported on a number of occasions; these reactions proceed most readily with electron-deficient alkenes, which is largely a consequence of the nucleophilicty of the stannyl radical. 6À12 For example, Podest a reported that reactions of (1R,2S,5R)-menthyldimethylstannane with diphenylpropenoates and propenenitriles (e.g., 3) take place with high levels of diastereoselectivity (Scheme 3), 10 while the addition of achiral trialkylstannanes to (1R,2S,5R)-menthyl crotonate (4) affords chiral tetraorganotin compounds with moderate diastereoselectivity (Scheme 3).…”
Section: ' Introductionmentioning
confidence: 99%
“…This reaction is believed to benefit from the increased rate of H-atom transfer, resulting from the in situ-generated polarity-reversal catalyst benzeneselenol. 55 Several neutral titanium complexes have been shown to catalyse intramolecular hydroamination reactions of alkenes. The corresponding pyrrolidine and piperidine products were formed in up to 97% yields.…”
Section: Additions Initiated By Metals and Metal Ions As Electrophilesmentioning
confidence: 99%
“…74 The first example of intermolecular Pd-catalysed aminoacetoxylation of alkenes, such as (52), with phthalimide as the nitrogen source and PhI(OAc) 2 as the stoichiometric oxidant and source of acetate has been reported. The reaction is highly regio-and diastereo-selective; mechanistic studies revealed that the reaction proceeds via syn-aminopalladation of the alkene [(52) → (53)], followed by oxidative cleav-de age of the intermediate Pd-C bond in the Pd(IV) intermediate (54) with an unusual inversion of stereochemistry to produce the threo-isomer (55). 75,76 The reaction is believed to commence by steering the approach of palladium by the alkoxy group [(56) →→ (57); R = Ar, Me, PhCH 2 ; R = Me, PhCH 2 ].…”
Section: Additions Initiated By Metals and Metal Ions As Electrophilesmentioning
confidence: 99%